The Impact of Shadowing Technique on Tertiary Students’ English Pronunciation - Rio Sugiarto; Prihantoro Prihantoro; Sarwo Edy (Linguists : Journal Of Linguistics and Language Teaching, 2020)
In the realm of English teaching and learning especially for those of non-native English users, English pronunciation instruction always calls for various techniques which can meet students’ conditions that are naturally affiliated with their psychological and cultural complexities. Thus, the present study aimed at examining the impact of one of English pronunciation instruction techniques, the so-called shadowing technique, on tertiary students’ English pronunciation at IAIN Curup, Bengkulu, Indonesia. An experimental study was conducted by engaging 40 tertiary English students selected randomly. They were split into two groups, wherein 20 students were taught English pronunciation using shadowing technique, and the rest 20 students were taught English pronunciation using a conventional technique. This study revealed that shadowing technique had a positive and significant impact on students’ English pronunciation. Their English pronunciation improvement encompassed various components such as monophthongs, diphthongs, triphthongs, semi-vowels, consonants, consonant cluster sounds, strong and weak forms, linking phonemes, syllable stresses, word stresses, sentence stresses, rhythm, pitch and intonation. Further studies are expected to scrutinize the effect of shadowing technique on English pronunciation by involving more samples, making use of gender difference as a moderator variable, and testing the retention of English pronunciation improvement.